DE-RADICALIZATION OF FUNDAMENTALISM THROUGH THE THOUGHT OF MOHAMMED ARKOUN - Rezan, Muhammad; Asnawi, Naupal (International Review of Humanities Studies, 2019)
Fundamentalism in religion has become an important issue in people's lives, especially in areas with high heterogeneity. The emergence of various cases of attacks against innocent people in the name of religion, has become an irony of its own, especially for religious believers. The irony arises when religion teaches peace in diversity, but there are many irregularities in its implementation. Various factors in the emergence of fundamentalism in religion do not necessarily become a reason for the lack of efforts to deradicalize this understanding. Mohammed Arkoun, through his various studies, has raised the significance of a re-understanding of religious texts with the present context. Relevance of religion - as a guideline for human life - is essential, especially in the current era of disruption. Based on these matters, this study was made to present the deradicalization of fundamentalism through a re-understanding of religious texts in a critical and integrated manner. Arkoun explained that the main problem in this matter was the effort to make religion an institutional product whose interpretation was absolute, which led to a single understanding. This incident is contrary to the concept of Islam as a religion that is rahmatanlilaminalamin (Islam as a religion that brings grace and prosperity to all people). By utilizing a disruption era that recognizes change quickly and radically, this moment can be used well to provide a comprehensive, integrated, and credible religious knowledge forum, and of course with a high level of accessibility.